2018
DOI: 10.1039/c8tc02457j
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of energy transfer in a polymer composite with perylene chromophores

Abstract: Luminescent solar concentrators based on molecular dyes are a promising approach to light collection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 46 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…In recent decades, researchers have attempted to create efficient light-harvesting antenna complexes. More recently, research studies have begun mimicking the energy cascade systems found in natural photon-driven structures. These systems aim to separate absorption and emission events via transferring energy from an accepter to an emitter through an energy-transfer process, such as the Förster resonance energy transfer (FRET). This has been achieved in both semiconductor heterostructured quantum dots and rods and organic dye systems. , We propose the creation of a hybrid organic/inorganic light-harvesting complex via the attachment of organic chromophore ligands to a semiconductor nanocrystal.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, researchers have attempted to create efficient light-harvesting antenna complexes. More recently, research studies have begun mimicking the energy cascade systems found in natural photon-driven structures. These systems aim to separate absorption and emission events via transferring energy from an accepter to an emitter through an energy-transfer process, such as the Förster resonance energy transfer (FRET). This has been achieved in both semiconductor heterostructured quantum dots and rods and organic dye systems. , We propose the creation of a hybrid organic/inorganic light-harvesting complex via the attachment of organic chromophore ligands to a semiconductor nanocrystal.…”
Section: Introductionmentioning
confidence: 99%
“… 20 , 45 49 The excimer-state emission generally comes from PDIs that exhibit H-aggregate formation facilitated by the addition of bulky groups attached to the imide positions of the PDI. 44 , 48 , 50 Understanding the formation of these low-energy excimer states in molecular aggregates is of great interest 11 , 51 , 52 as it could allow for increased functionality, stability, and device performance. The excimer state can act as an exciton trap site, decreasing the quantum yield or device performance if the trapping occurs at a faster rate than exciton diffusion, 53 , 54 charge transfer, and transport.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their extensive π-systems, at high concentrations, PDIs regularly form H or J aggregates, as well as excimer-like states. , H-aggregates are characterized by face-on stacking, blue-shifted absorption, and quenched luminescence, whereas J aggregates form from edge-on stacking and have red-shifted luminescence. , The role of the excimer state in PDIs has been extensively studied. , The excimer-state emission generally comes from PDIs that exhibit H-aggregate formation facilitated by the addition of bulky groups attached to the imide positions of the PDI. ,, Understanding the formation of these low-energy excimer states in molecular aggregates is of great interest ,, as it could allow for increased functionality, stability, and device performance. The excimer state can act as an exciton trap site, decreasing the quantum yield or device performance if the trapping occurs at a faster rate than exciton diffusion, , charge transfer, and transport. , …”
Section: Introductionmentioning
confidence: 99%
“…6 In recent decades, lumophores with high PLQYs and excellent stabilities, such as quantum dots, 7,8 metal complexes 9,10 and organic dyes, 11,12 have been developed. In particular, πconjugated polymers have been extensively investigated as lumophores for flexible, light-weight optical devices such as field-effect transistors, 13,14 organic light-emitting diodes, 15,16,17 and PV devices, 18,19 as well as LSCs, 20,21 due to their desirable optoelectronic properties and costeffective solution processability. 22 However, the optical efficiency of conjugated polymers is often undermined by aggregation-caused quenching (ACQ), which occurs due to preferential nonradiative relaxation of excited states as a result of intermolecular π-π interactions.…”
Section: Introductionmentioning
confidence: 99%